Applying concept of species in the botanical taxonomy - Ly, Tran Dinh; Bach, Tran The (Academia Journal of Biology, 2015)
Species (eidos) is fundamental discussed problem in systematics and evolutionary theory. There are now about 20 different concepts of species, e.g. morphological species of Linné (1753), evolutionary species of Simpon (1961), phylogenese species of Schwarz (1936), ecological species and agamospecies of Turesson (1922), universal species of Sawadski (1968), geo-morphological species or taxonomical species of Grant (1957, 1963). Each definition is based on researched results of determinate side by separate method. Two important criteria used to distingwish species are morphological interruption and sexual reproductive isolation. All of concepts reflect a part of content of species. Concept of universal species reflects all-sides contents of species only. Applying taxonomical species in practice is more benificial, because of criteria for distingwish species are morphological signs, which are easy to identify by eye or with modern instruments. Almost of experimental controls show coincidence of morphological species with biological species.